Depression Symptoms and Cognitive Test Performance in Older American Indians: The Strong Heart Study - Suchy-Dicey, Astrid (J Am Geriatr Soc, 2020)
BACKGROUND: American Indians have excess risk of depression, which can contribute to cerebrovascular and cognitive disability, with effects on memory, processing speed, executive function, and visuospatial ability. However, studies examining depression and cognition in American Indians are limited; this study aims to report associations of depression with general cognition, verbal fluency and memory, and processing speed. DESIGN: Cohort study. SETTING: The Cerebrovascular Disease and its Consequences in American Indians study was an ancillary examination of Strong Heart Study participants from 3 U.S. regions. PARTICIPANTS: All eligible were included in this analysis (N=818). MEASUREMENTS: Participants completed evaluations for depressive symptomology, cognition, and physical function—including Center for Epidemiologic Studies Depression (CESD), Modified Mini-Mental State Examination (3MSE), Wechsler Adult Intelligence Scale-Fourth Edition coding (WAIS), Controlled Oral Word Association (COWA), California Verbal and Learning Test, Halstead finger tapping, grip strength, and Short Physical Performance Battery (SPPB) tests. Linear mixed models were adjusted for site, age, sex, education, income, marital status, alcohol, smoking, diabetes, hypertension, obesity, cholesterol, stroke, infarct, and hemorrhage. RESULTS: Symptoms of depression were common, with 20% (N=138) endorsing CES-D scores of 16+. More depressive symptoms were associated with older age, female sex, lower education, lower income, non-married status, not using alcohol, not smoking, hypertension, diabetes, and stroke. In adjusted analyses, processing speed (WAIS: β −0.13, 95%CI −0.25, −0.03), general cognition (3MSE: β −0.10, 95%CI −0.17, −0.03), verbal fluency (COWA: β −0.10, 95%CI −0.19, −0.01), and motor function (SPPB: β −0.05, 95%CI −0.07, −0.03) were significantly associated with more symptoms of depression. CONCLUSION: These findings maybe informative for health disparities populations, especially those with depressive risk. Clinicians may require particular training in cultural humility. Future studies should validate use of the CES-D scale in this population; longitudinal studies may focus on causal mechanisms and potential secondary prevention, such as social support.